Transcriptomic analysis of the response of Avena sativa to Bacillus amyloliquefaciens DGL1 - Yang, Xue; Xie, Yongli; Wang, Tian; Qiao, Youming; Li, Junxi; Wu, Lingling; Gao, Ying (Frontiers in Microbiology, 2024)
Bacillus amyloliquefaciens DGL1, isolated from the arid sandy land ofareas in Dagler, Qinghai Province, China, was shown to promotepromotes the growth of Avena sativa variety 'Qing Yan 1'. To elucidate the transcriptometranscriptomic changes in the oat root system after strain DGL1 interactsfollowing interaction with oatDGL1 and to reveal the molecular mechanism ofby which DGL1's promotion of promotes oat growth, this study analyzed the transcriptome between the treatment and control (CK) groups of oat roots at 2, 4, 8, and 12 h after inoculation with a strain DGL1 suspension of strain DGL1 were analyzed using Illumina high-throughput transcriptome sequencing technology. The differentially expressed genes were analyzed bydetermined through Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, and the metabolic pathways and key genes of the differentially expressed genes in oat roots were analyzed. The results showed that 7874, 13,392, 13,169, and 19,026 differentially expressed genes were significantly enriched in the glycolysis/gluconeogenesis pathway, amino acid metabolism, nitrogen metabolism, plant hormone signal transduction, and other related metabolic pathways in the oat roots at 2, 4, 8, and 12 h after inoculation with a DGL1 suspension, respectively.. The GO and KEGG enrichment analysisanalyses revealed that the genes encoding plasma membrane ATPase, phosphoglycerate kinase gene PGK, ammonium transporter protein gene AMT, cellulose synthase gene CSLF6, and growth hormone response family gene IAA18 were significantly upregulated. It is hypothesized that the pro-growth mechanism of strain DGL1 onin oats is the result of the coordination of multiple pathways through the promotion of oat energy metabolism, phytohormone signaling, secondary metabolite synthesis, and amino acid metabolism.